Does dropping day 5 PEP follow-up affect outcomes? An audit of HIV post-exposure prophylaxis at a central London sexual health clinic. (July 2015) - O'Keeffe, C; Nwokolo, N; McOwan, A; Whitlock, G
UK post-exposure prophylaxis (PEP) guidelines were updated by the British Association for Sexual Health and HIV (BASHH) in 2011. In 2013, we changed policy to omit day 5 PEP follow-up at 56 Dean Street as it was felt clinically unnecessary. This audit compares our performance against BASHH standards for PEP attenders during June 2012 and June 2013. We identified 162 PEP prescriptions; PEP assessment and appropriate sexually transmitted infection testing was done well. PEP completion rates and post-PEP HIV testing were lower than BASHH standards. Following omission of day 5 review, documentation that results have been checked was poor; however, attendance at follow-up was not adversely affected.